PCM-enhanced Lime Plasters for Vernacular and Contemporary Architecture. (November 2016) - Theodoridou, Magdalini; Kyriakou, Loucas; Ioannou, Ioannis
Abstract: Phase Change Materials (PCMs) have the ability to absorb and release thermal energy, in the form of latent heat, during the melting or solidifying processes respectively. Thus, they may be used as additives in the production of thermally efficient composite building materials, such as plasters. This paper focuses on the design and production of PCM-enhanced lime plasters with significantly low thermal conductivity and increased specific heat capacity. The aforementioned plasters are appropriate for application in southern European climatic conditions. Due to their compatibility with traditional substrate materials, they may also be used for the renovation and retrofitting of existing structures.